Between Communication and Information - Ruben, Brent D. (Taylor and Francis, 2017)
"The current popularity of such phrases as "information age" and 'information society" suggests thatlinks between information, communication, and: behavior have become closer and more complex in a technology-dominated culture. Social scientists have adopted an integrated approach to these concepts, opening up new theoretical perspectives on the media, social psychology, personal relationships, group process, international diplomacy, and consumer behavior. Between Communication and Information maps out a richly interdisciplinary approach to this development, offering innovative research and advancing our understanding of integrative frameworks. This fourth volume in the series reflects recently established lines of research as well as the continuing interest in basic areas of communications theory and practice. In Part I contributors explore the junction between communication and information from various theoretical perspectives, delving into the multilayered relationship between the two phenomena. Cross-disciplinary approaches in the fields of etymology and library science are presented in the second section. Part III. brings together case studies that examine the interaction of information and communication at individual and group levels; information exchanges between doctors and patients, children and computers, journalists and electronic news sources are analyzed in depth. The concluding segment focuses on large social contexts in which the interaction of communication and information affects the evolution of institutions and culture. Between Information and Communication both extends and challenges current thinking on the mutually supporting interplay of information and human behavior. It will be of interest to sociologists, media analysts, and communication specialists."--Provided by publisher